2019
DOI: 10.21203/rs.2.12764/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rural vs urban residence and experience of discrimination among people with severe mental illnesses in Ethiopia

Abstract: Background Few studies have addressed mental illness-related discrimination in low-income countries, where the mental health treatment gap is highest. We aimed to evaluate the experience of discrimination among persons with severe mental illnesses (SMI) in Ethiopia, a low-income, rapidly urbanizing African country, and hypothesised that experienced discrimination would be higher among those living in a rural compared to an urban setting. Methods The study was a cross-sectional survey of a community-ascertai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…87 Minorities, including mentally ill persons or sexual minorities, may challenge with violence, more in urban settings than in rural ones, mostly derived by a politically oriented discrimination and leading to more social stress and psychopathology. [87][88][89] Specific mental health services should be developed for mental health issues related to the state of being minority or migrant minority, also specific training on these issues should be introduced in the core curriculum of mental health care professionals. 85…”
Section: Relationship Between Mental Illness and Social Classmentioning
confidence: 99%
“…87 Minorities, including mentally ill persons or sexual minorities, may challenge with violence, more in urban settings than in rural ones, mostly derived by a politically oriented discrimination and leading to more social stress and psychopathology. [87][88][89] Specific mental health services should be developed for mental health issues related to the state of being minority or migrant minority, also specific training on these issues should be introduced in the core curriculum of mental health care professionals. 85…”
Section: Relationship Between Mental Illness and Social Classmentioning
confidence: 99%
“…According to a qualitative study which involved 26 mental health practitioners or educators, participants perceived community stigma as soon as individuals with severe mental illness were seen outside their homes, regardless of gender [38]. In a population-based study among people with severe mental illness, 63.3% of 300 participants had experienced discrimination in the previous year, mainly by being avoided or shunned because of mental illness [43]. An institution-based study in an urban setting reported similar ndings of perceived stigma (62.6%) among 423 people with schizophrenia [44].…”
Section: Public Stigmamentioning
confidence: 99%